2018
DOI: 10.1126/science.aar8174
|View full text |Cite
|
Sign up to set email alerts
|

An ER surface retrieval pathway safeguards the import of mitochondrial membrane proteins in yeast

Abstract: The majority of organellar proteins are translated on cytosolic ribosomes and must be sorted correctly to function. Targeting routes have been identified for organelles such as peroxisomes and the endoplasmic reticulum (ER). However, little is known about the initial steps of targeting of mitochondrial proteins. In this study, we used a genome-wide screen in yeast and identified factors critical for the intracellular sorting of the mitochondrial inner membrane protein Oxa1. The screen uncovered an unexpected p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
173
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(199 citation statements)
references
References 28 publications
(29 reference statements)
17
173
0
2
Order By: Relevance
“…Recently, an unexpected pathway of targeting mitochondrial membrane proteins, termed ER-surface mediated protein targeting (ER-SURF), was discovered in yeast (Hansen et al, 2018). ER-SURF helps to retrieve mitochondrial proteins from the ER surface and transfers them to mitochondria (Fig.…”
Section: Alternative Routes For Protein Import Into Mitochondriamentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, an unexpected pathway of targeting mitochondrial membrane proteins, termed ER-surface mediated protein targeting (ER-SURF), was discovered in yeast (Hansen et al, 2018). ER-SURF helps to retrieve mitochondrial proteins from the ER surface and transfers them to mitochondria (Fig.…”
Section: Alternative Routes For Protein Import Into Mitochondriamentioning
confidence: 99%
“…This is promoted by the ER-localized chaperone Djp1 that cooperates with the mitochondrial pre-protein receptors Tom70 and Tom71 in this process. Through ER-SURF, Djp1 imports the inner membrane protein Oxa1 (in a precursor and import-competent state) into mitochondria (Hansen et al, 2018). Various mechanisms protect cells from proteotoxic stress induced by the accumulation of precursor proteins in the cytosol, including the stabilization of precursor proteins by cytosolic chaperones and ubiquilins (Itakura et al, 2016;Young et al, 2003), and the proteasomal degradation of over-accumulated proteins (Wrobel et al, 2015).…”
Section: Alternative Routes For Protein Import Into Mitochondriamentioning
confidence: 99%
See 1 more Smart Citation
“…Whether ubiquitin ligases are involved and at what step they act to mediate Msp1-mediated degradation is not known. Mistargeted proteins can also be rescued, as exemplified by a pathway from the ER to mitochondria involving the chaperone Djp1 (Hansen et al 2018). Misloc.…”
Section: Membrane Monitors Of Protein Mislocalizationmentioning
confidence: 99%
“…Recently, it was shown that some mitochondrial membrane proteins mistargeted to the ER membrane are not degraded, but rather retrieved for successful import into mitochondria (Hansen et al 2018). An ER-localized factor called Djp1 is required for this retrieval pathway.…”
Section: Recognition and Degradation Of Mislocalized Proteinsmentioning
confidence: 99%